ChemInform Abstract: Solution‐Phase Synthesis of Cesium Lead Halide Perovskite Nanowires. Issue 46 (November 2015) - Zhang, Dandan; Eaton, Samuel W.; Yu, Yi; Dou, Letian; Yang, Peidong
Abstract CsPbX3 (X: Br, Cl, I) nanowires (NWs) are prepared by a catalyst‐free, solution‐phase reaction of Cs oleate and PbX2 in presence of oleic acid and oleylamine in octadecene (standard Schlenk technique, 150‐250 °C, 1 h).